2016
DOI: 10.4103/0971-5916.178616
|View full text |Cite
|
Sign up to set email alerts
|

Profile of female patients seeking in-patient treatment for prescription opioid abuse from a tertiary care drug dependence treatment centre from India

Abstract: Background & objectives:There has been a limited focus on prescription drug abuse among women in the country. Choice of psychoactive substance, reasons for initiation and co-occurring disorders have been found to be different among men and women. The current study was aimed at studying the profile of female patients seeking in-patient treatment for prescription drug use over a period of five years at a tertiary care drug dependence treatment centre in India.Methods:Case records of all female patients admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
(24 reference statements)
2
3
0
Order By: Relevance
“…The present study showed that socio-demographic variables of marital, employment and socio-economic status of women who sought in-patient care, majority of them were housewives, married and low socio-economic background; this finding was similar to results of previous studies (Atul 2017, Kanika 2017, Dayal 2016 , Grover 2015). Most of them come to treatment on their own or brought by family members, , and some of them referred by a psychiatrist.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study showed that socio-demographic variables of marital, employment and socio-economic status of women who sought in-patient care, majority of them were housewives, married and low socio-economic background; this finding was similar to results of previous studies (Atul 2017, Kanika 2017, Dayal 2016 , Grover 2015). Most of them come to treatment on their own or brought by family members, , and some of them referred by a psychiatrist.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, nearly half of them was not using more than one substance. Common co-morbidity psychiatric illness was depression in this study, similar to previous Indian studies ( Dayal 2016 , Arnaudo et al 2017 , Nebhinani et al 2013 and Ray et al 2004 ). More than half of them did not have any psychiatric co-morbidity condition in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“… 4 Nearly half of the women treatment-seekers in tertiary addiction treatment centres or community clinics in India also report similar psychosocial issues for initiation of substance use. 5 6 7 Treatment seeking and retention are usually poor among women all over the world including India. 5 6 Studies indicate that women face various systemic, structural, social and individual barriers in treatment seeking and retention in treatment for substance abuse.…”
Section: Introductionmentioning
confidence: 99%